Ketahanan Beberapa Varietas Padi Lokal terhadap Virus Tungro Isolat Muara - Ruimassa, Reymas; Manzila, Ifa; Temaja, I Gede Rai Maya; Sudana, I Made (Jurnal Fitopatologi Indonesia, 2022)
Resistance of Several Local Rice Varieties to Isolate Tungro Virus from MuaraTungro disease is one of the important diseases in rice because it causes stunted plants and may induce significant yield losses. Planting resistant varieties is a recommended control strategy to overcome tungro disease. The research was conducted to find sources of genetic resistance from local rice varieties that can be used in breeding of tungro disease resistant varieties. The experiment was arranged in a descriptive research design with observational techniques. Observations were made on 16 local rice varieties with each variety consisting of 30 sample plants so that the number of plants used was 480 plants. The isolate of tungro virus collected from rice field in Muara, Bogor was inoculated to the test plants through the insect vector, green leafhopper (Nepothettix virescens). The results showed that the resistance of local varieties varied based on the value of disease index, disease incidence and plant height reduction. ‘TN1’ was the check susceptible variety against tungro virus, while the local rice varieties were differentiated into resistant (‘Utri Merah’), moderate (‘Karau’, ‘Bekongan’, ‘Bujang Bernai’, ‘Srogel Abang’, ‘Pulut Garu’, ‘Randu Range’, ‘Siredep’, ‘Katimpung’, ‘Pulut Sawijan’, ‘Dube’), moderate tend to be susceptible (‘Blumbungan’, ‘Tjere bandung’, ‘Sempor’) and susceptible (‘Rumbai’). All varieties can be infected (disease incidence 27 – 76%), but disease severity varies greatly (3–7). The more severe the disease, the higher the plant height reduction. ‘Srogel Abang’ is a variety that is useful for breeding rice varieties resistant to tungro disease because it showed moderate response with a low percentage of plant height reduction (36%) so that plant productivity can still be maintained.